Measuring CMB Spectral Distortions from Antarctica with COSMO: Blackbody Calibrator Design and Performance Forecast - Mele, L.; Battistelli, E. S.; de Bernardis, P.; Bersanelli, M.; Columbro, F.; Coppi, G.; Coppolecchia, A.; D'Alessandro, G.; De Petris, M.; Franceschet, C.; Gervasi, M.; Lamagna, L.; et al. (Journal of Low Temperature Physics, 2022)
COSMO is a ground-based instrument to measure the spectral distortions (SD) of the Cosmic Microwave Background (CMB). In this paper, we present preliminary results of electromagnetic simulations of its reference blackbody calibrator. HFSS simulations provide a calibrator reflection coefficient of R similar to 10(-6), corresponding to an emissivity epsilon = 1 - R = 0.999999. We also provide a forecast for the instrument performance by using an ILC-based simulation. We show that COSMO can extract the isotropic Comptonization parameter (modeled as vertical bar y vertical bar = 1.77 . 10(-6)) as vertical bar y vertical bar = (1.79 +/- 0.19) . 10(-6), in the presence of the main Galactic foreground (thermal dust) and of CMB anisotropies, and assuming perfect atmospheric emission removal.